Biochemical and Anatomical Predictors of Endometrial Receptivity in IVF Patients with Haematological Disorders - Mahvish Javed, Muhammad Razaq, Syed Mohammad Tahir Shah, Chaman Ara, Nusrat Fozia Pathan, Khalid Shehzad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Women suffering from disorders of the blood have specific difficulties with ‘implantation in the context of in vitro fertilization (IVF)’ because of vascular or hormonal system challenges. Gaining insight into what impacts endometrial receptivity in this population may assist in formulating optimized approaches for their management.To evaluate the biochemical and anatomical predictors of endometrial receptivity and their association with IVF outcomes in women with haematological conditions. Methods: This observational study took place at Hayatabad Medical Complex, Peshawar, from January 2021 to January 2022. It included 79 women with different types of blood disorders who were undergoing IVF treatment. Each participant was evaluated for endometrial receptivity using ultrasound contouring ,including assessment of the endometrium’s thickness, its pattern, vascularity plus hormonal Prole (estradiol, progesterone, TSH, and prolactin). The outcomes of IVF showed fertilization rates along with ‘emerging embryo quality as well as their implantation and live birth rates that there were differences between receptive and non-receptive groups’. Results: Patients with receptive endometrium were significantly younger and had a shorter duration of infertility. Higher levels of estradiol and progesterone and lower TSH and prolactin were associated with receptivity. Sonographic parameters including greater endometrial thickness, trilaminar pattern, and enhanced vascular flow strongly correlated with successful implantation and live birth. Clinical pregnancy and live birth rates were significantly higher in the receptive group (p< 0.05). Conclusion: Endometrial receptivity in IVF patients with haematological disorders is closely linked to specific hormonal and anatomical markers. Incorporating these assessments into routine IVF protocols can enhance treatment success and guide individualized care. Keywords: Endometrial Receptivity; In Vitro Fertilization; Haematological Disorders; Estradiol; Endometrial Thickness; Doppler Ultrasound; IVF Outcomes